Application of Problem Based Learning Learning Model in Improving Mathematics Learning Outcomes of Class VIII Students of State Junior High School 1 Ulugawo Academic Year 2021/2022 - Tafonao Sotanius; Sadiana Lase; Yakin Niat Telaumbanua (CV. Rayyan Dwi Bharata, 2002)
Based on the results of preliminary observations at the Ulugawo State Junior High School 1, several problems were found, including: 1) Learning is still conventional (teacher centered), and 2) Student learning outcomes in mathematics subjects are still lacking. Research objectives: (1) Describe the quality of mathematics learning through the application of the Problem Based Learning learning model. (2) Describe student learning outcomes in mathematics subjects through the application of the Problem Based Learning learning model. The research location is at Ulugawo State Junior High School 1. The subjects of the study were 26 students of classVIII-A, consisting of 10 men and 16 women. The research method used is Class Action Research (PTK) which consists of four stages, namely: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. Research instruments: (1) Observation sheets, (2) Learning quality questionnaires, (3) Student learning outcomes tests (4) Interview guide sheets, and (5) Photo documentation. Research results: (1) The quality of mathematics learning through the application of the Problem Based Learning learning model at the State Junior High School 1 Ulugawo for the 2021/2022 Academic Year in Cycle I, which is 64.39% classified as sufficient criteria and in Cycle II, 98.53% is classified as very good criteria. (2) The average student learning outcomes in mathematics subjects through the application of the Problem Based Learning learning model at the State Junior High School 1 Ulugawo for the 2021/2022 Academic Year in Cycle I are 69.30 classified as sufficient criteria and in Cycle II, 80.15 are classified as good criteria.